The Role of Protein Synthesis Disorders in Hereditary Diseases (Literature Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article analyzes the causes, molecular mechanisms, and clinical manifestations of hereditary diseases resulting from protein synthesis disorders. Genetic mutations disrupt various stages of protein synthesis—transcription, translation, and posttranslational modifications—as a result of which vital proteins are not produced in sufficient quantities or in the correct structure in the body. The article highlights the pathological consequences of these processes using the examples of diseases such as phenylketonuria, cirrhosis, cystic fibrosis, and Hemophilia. The study reveals the role of protein synthesis disorders in the pathogenesis of hereditary diseases and the possibilities of early diagnosis and gene therapy in medicine.